FRACTAL ONTOLOGY AND ANARCHIC SELFHOOD: MULTIPLICITOUS BECOMINGS - Jaques, William S. (My University, 2013)
This thesis explores the notion of selfhood and its relationship to larger philosophical frameworks. In Chapter One the author traces various understandings of the self as they have appeared historically in Western philosophy. This understanding of the self posits it as something static and unchanging. The author argues that this was largely the result of certain ontological or metaphysical commitments of the broader philosophical frameworks in which the self was situated. In Chapter Two Deleuze's ontology is explored as an alternative to what the author takes to be typical Western ontologies. It is argued that Deleuze's 'fractal ontology' is radically different because it begins and ends with multiplicity and becoming. This new understanding of ontology provides the basis for understanding the self as multiplicitous and anarchic rather than static and essentialist. In the final chapter, the author seeks to explore the resulting understanding of selfhood as decentralized and multiplicitous. It is asserted that such an understanding of the self is philosophically compelling given the new Deleuzian ontology. It is further argued that this understanding of the self is practically superior to traditional static understandings of the self because it more fully accommodates personal and societal growth.
Keywords: Ontology; Deleuze; Anarchism; selfhood; multiplicity; becoming; Continental Philosophy; Other Philosophy; Continental Philosophy